Assessing the mechanism of oil price fluctuation and fiscal policy response in the Malaysian economy - Nora Yusma Mohamed Yusoff (Penerbit Universiti Kebangsaan Malaysia, 2013)
The present paper analyzes the effects of oil price fluctuation on the economy;and fiscal policy response to the Malaysian economy. The data are analyzed utilizing a co-integration test, variance decomposition (VDC) and impulse response function (IRF) analysis under the unrestricted vector autoregression (VAR) methodology. The empirical findings of this study suggest that, in the short run, the Malaysia economy benefits from higher oil prices, as oil price shocks positively affect oil revenue. However, the real GDP of Malaysia is vulnerable to oil price fluctuations in the short term horizon. Meanwhile, oil price hikes exhibit an increasing trend for both GDP and total subsidy in the long run. Also, the results confirm that the changes in world oil prices have a significant short term impact on total government expenditure. These confirm that that fiscal policy is the main mechanism channel that determines the degree to which oil price shocks affect the economy. The study suggests that the adoption of expansionary fiscal policies during oil price shocks can facilitate rapid economic growth in the long run, as long as stable and persistent economic policies exist within the macroeconomic framework.